Transducers in mechanical and electronic design - Trietley, Harry L. (Mechanical engineering (Marcel Dekker, Inc.), 1986)
This single-source reference provides vital information on the operation, features, circuits, and applications of various transducers, including those used in temperature, pressure, position, flow, vibration, shock, acceleration, conductivity, pH, and other measurements.